PENGEMBANGAN BAHAN AJAR DIGITAL INTERAKTIF DENGAN PENDEKATAN MULTI REPRESENTASI PADA MATERI BILANGAN BULAT UNTUK SISWA SMPLB TUNARUNGU KELAS VII - Gede Pande Suarcita; I Wayan Puja Astawa; I Made Suarsana (Akademika, 2020)
This research is purposed to (1) Created interactive digital teaching materials design with a multi-representation approach to integer material for the seventh grade deaf students of SMPLB. (2) Described the results of the prototype of interactive digital teaching materials with a multi-representation approach to integer material for the seventh grade deaf students of SMPLB. (3) Knew the usability of interactive digital teaching materials with a multi-representation approach to integer material for the seventh grade deaf students of SMPLB. This research used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Product trial test is carried out limited to feasible, efficient, and effective. This research was conducted at SLB Negeri1 Buleleng. The results of this research indicate the average score of the material expert is 2.92, the linguistic expert is 2.85, the presentation expert is 3.00, and the graphic expert is 3.00 which means that the developed interactive digital teaching material has decent criteria. The response given by the teacher and students is very good with an average score from the teacher's questionnaire responses is 4.60 and the average score of student questionnaire responses is 4.30 so that interactive digital teaching materials developed are said to be efficient. The effectiveness of the developed interactive digital teaching materials is said to be effective based on cognitive ability test results by students. The classical completeness of 87.5% with the highest value obtained by 90 and the lowest value of 70